2023
DOI: 10.1039/d2na00767c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a crystalline zeolitic imidazole framework-8 nano-coating on single environment-sensitive viral particles for enhanced immune responses

Abstract: Encapsulating antigens by zeolitic imidazole framework-8 (ZIF-8) exhibits many advantages in vaccine development. However, most viral antigens with complex particulate structures are sensitive to pH or ionic strength, which cannot...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…1500 nm, which was consistent with the morphology of UiO-67 reported in the literature [48,49]. During the process of crystallization, CTAB was adsorbed on the surface of the UiO-67 primary crystal, which would decrease the van der Waals force and surface energy, promoting the ordered agglomeration, thus forming a more regular morphology [50][51][52]. The long hydrocarbon chains of CTAB also repelled each other, preventing the further interaction with other UiO-67 crystals and excessive growth of UiO-67, resulting in a smaller particle size [53,54].…”
Section: Synthesis and Characterizationsupporting
confidence: 87%
See 1 more Smart Citation
“…1500 nm, which was consistent with the morphology of UiO-67 reported in the literature [48,49]. During the process of crystallization, CTAB was adsorbed on the surface of the UiO-67 primary crystal, which would decrease the van der Waals force and surface energy, promoting the ordered agglomeration, thus forming a more regular morphology [50][51][52]. The long hydrocarbon chains of CTAB also repelled each other, preventing the further interaction with other UiO-67 crystals and excessive growth of UiO-67, resulting in a smaller particle size [53,54].…”
Section: Synthesis and Characterizationsupporting
confidence: 87%
“…This may be owing to the fact that most CTAB existed as micelles, rather than dispersed forms, which did not interact well with surfaces [51,55]. Wang et al [52] also reported that the morphology and size of 146S@ZIF-8 can be changed by adding CTAB. Jubeer et al [56] reported that the particle size of ZnS could be adjusted by changing the concentration of CTAB.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Compared with ionic liquids and other organic solvents, surfactants possess higher thermal and chemical stability and lower vapor pressure . Strategies for the assisted synthesis, regulation, and control of multifunctional monolithic MOFs with surfactants such as polyvinylpyrrolidone (PVP), polyethylene glycol-400 (PEG-400), and cetyltrimethylammonium bromide (CTAB) have gained extensive research interest …”
Section: Synthetic Methods For Monolithic Mofsmentioning
confidence: 99%
“…43 Strategies for the assisted synthesis, regulation, and control of multifunctional monolithic MOFs with surfactants such as polyvinylpyrrolidone (PVP), polyethylene glycol-400 (PEG-400), and cetyltrimethylammonium bromide (CTAB) have gained extensive research interest. 44 In 2018, Liu et al prepared ultrathin MOF nanosheets using a surfactant-assisted (PVP) method and then loaded them on flexible porous supports via vacuum filtration, finally producing flat ZnTCPP-MOF nanolayers for the separation of CO 2 (Figure 3), CO 2 transmittance ∼2100 GPU, and CO 2 /N 2 ideal selectivity ∼30. In summary, the as-prepared grooved layer of porous MOF nanosheets can significantly reduce the gas transport resistance, thereby maximizing the gas flux of the composite membrane.…”
Section: Synthetic Methods For Monolithic Mofsmentioning
confidence: 99%
“…The polar groups in His strengthened hydrogen bond formation with solvent water molecules, creating a hydrated shell on the Ad5@His-aZn-mIM surface, further enhancing its conformational stability at high temperatures ( Figure 2 f,g). Recently, Wang et al successfully synthesized crystalline ZIF-8 on foot-and-mouth disease virus by pre-lowering the pH of the 2-mIM solution to 9.0 [ 75 ]. The encapsulated viral vaccine induced approximately ten times higher antibody titers and significantly increased cellular immune responses in mice.…”
Section: Biointerface Engineeringmentioning
confidence: 99%